REIMAJINASI MANAJEMEN PENDIDIKAN: INTEGRASI NILAI MODERASI BERAGAMA DALAM KEPEMIMPINAN SEKOLAH ISLAM: Studi Kasus di MI Tarbiyatul Islamiyah Rejotangan - Ahmad Fahrudin (IAIN PONOROGO, 2026)
This study aims to analyze the integration of religious moderation values into Islamic educational management through the leadership of the Headmaster of Madrasah at MI Tarbiyatul Islamiyah Rejotangan. The study employs a qualitative approach with a case study design. Research informants—purposively selected—consist of headmaster of madrasah, 6 teachers, 11 students, school board, and 2 of parents. Data were collected through in-depth interviews, participant observation, and document analysis, and subsequently analyzed using an interactive model comprising data reduction, data display, and conclusion drawing and verification. The results indicate that religious moderation values are systematically integrated into the planning, organizing, implementation, and evaluation functions of educational management. At the planning stage, moderation values are internalized within the madrasah's vision, mission, and programs; at the implementation stage, they are manifested through instruction, habituation, and inclusive religious activities; meanwhile, evaluation is conducted through supervision, reflection, and monitoring of students' character development. The headmaster of madrasah’s transformational and participatory leadership serves as a key factor in fostering collaboration among the school community and strengthening a school culture that is tolerant, inclusive, and oriented toward character building. These findings demonstrate that the integration of religious moderation into Islamic educational management transcends normative values, manifesting instead in managerial practices that support the creation of a harmonious and sustainable learning environment.